PENGARUH PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT BAKRIE SUMATERA PLANTATION, Tbk SERBANGAN ESTATE, KISARAN - Sherly Sherly; Edy Dharma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2020)
The objective of this research is to measure the influence of controlling on employee performance at PTBakrie Sumatera Plantation, Tbk Serbangan Estate, Kisaran. The population of this research is 164employees who work at PT Bakrie Sumatera Plantation, Tbk Serbangan Estate, Kisaran and the sample are62 employees. The sample is taking according to Slovin method. Analysis technique use liniar regressionmethod with SPSS versi 21. Based on t-test, controlling has positive and significant influence to employeeperformance. This is evidenced by the regression results Y = 15,808 + 0,340 X.